Influenza and Pregnancy: A Review of the Literature from India - Simmerman, James Mark; Arya, Saurabh; Chhabra, Pankdeep; Bhalerao-Gandhi, Ashwini (Infectious Diseases in Obstetrics and Gynecology, 2015)
Maternal influenza infection is known to cause substantial morbidity and mortality among pregnant women and young children. Many professional healthcare bodies including the World Health Organization (WHO) have identified pregnant women as a priority risk group for receipt of inactivated seasonal influenza vaccination. However influenza prevention in this group is not yet a public health priority in India. This literature review was undertaken to examine the Indian studies of influenza among pregnant women. Eight Indian studies describing influenza burden and/or outcomes among pregnant women with influenza were identified. In most studies, influenza A (pH1N1) was associated with increased maternal mortality (25–75%), greater disease severity, and adverse fetal outcomes as compared to nonpregnant women. Surveillance for seasonal influenza infections along with higher quality prospective studies among pregnant women is needed to quantify disease burden, improve awareness among antenatal care providers, and formulate antenatal influenza vaccine policies.